Pengaruh Struktur Modal dan Kebijakan Dividen Terhadap Kinerja Keuangan: Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di BEI Tahun 2020-2023 - Najwa Rani Angel; Salma Taqwa (Universitas Negeri Padang, 2026)
This research examines the influence of capital structure and dividend policy on firms’ financial performance. A quantitative approach with a causal research design was employed in this study. The population consisted of non-cyclical consumer companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The sample was determined through purposive sampling, resulting in 40 companies with 120 observational data points. The research utilized secondary data obtained from the published annual reports of the companies. Financial performance was measured using ROA, while capital structure was proxied by the Debt-to-Equity Ratio (DER) and dividend policy was measured using the Dividend Payout Ratio (DPR). The findings indicate that capitali. structure negatively influences financial performance, whereas dividend policy positively affects financial performance.